Chronic Inflammatory Demyelinating Polyneuropathy: Time to Maximal Recovery in Patients Receiving Intravenous Immunoglobulin Therapy. (13th July 2020) - Opala, Adrian R.; Kennedy, Kevin; Baker, Steven K.
ABSTRACT: Background: The response of chronic inflammatory demyelinating polyneuropathy (CIDP) to intravenous immunoglobulins (IVIgs) treatment is well established. However, it remains unclear whether patients not responding to two IVIg treatments or those whose condition stabilizes (ICE trial) may benefit from additional doses. We aim to identify the time period required to reach maximal strength gains from IVIg treatment. Methods: Retrospective chart review of 14 patients with CIDP was performed. Change in handgrip (HG), Knee extension (KE), elbow flexion, and dorsiflexion was analyzed with a dynamometer during IVIg therapy. Strength improvements in Nm or kg, cumulative grams (g) of IVIg, and time in days required for maximal strength recovery were determined per function (± standard error of the mean). Ancillary therapy was recorded for all patients. Results: Improvements in strength of each function were significant (p < 0.05). Earliest improvement was in HG (137.07 ± 21.23) and latest in KE (238.15 ± 38.9). Majority of patients improved by 200 days of therapy. HG required the lowest cumulative grams of IgG (561.71 ± 97.21) and KE the most (798 ± 120.7). Conclusion: Our study has demonstrated the effectiveness of multiple treatments with IVIg to reach significant improvement in strength. Different muscle groups manifested different time dependency, reflecting the requirement of variable amounts of IVIg. Improvement was identified on an ongoing basis, with therapy lasting between 20.2 and 37.3 weeks, requiring between 562 and 798 g of IVIg.